CONSERVATIVE MUSLIM ON THE SCREEN: The Narrative of Islamic Family Law in Indonesian Films - Hadi, Mukhammad Nur (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2021)
This article focuses on the paradigm of Islamic family law in four Indonesian Islamic films: When Cinta Bertasbih 2 (2009), The Unmissable Heaven (2015), Talak 3 (2016), and Wedding Agreement (2018). This article brings a discussion of family law issues that were constructed in these films, with the purpose to find out what kind of family law tendencies are presented. This research utilizes a qualitative content analysis approach. It means the data was collected by examining scene by scene related to family law issues in the four films and then analyzed. As a result, this article argues that a variety of Islamic family law issues, including unregistered marriage, polygamy, triple talaq, and marriage agreements in the films, tend to result in conservative rather than progressive fiqh. This demonstrates that there is an attempt (wittingly/unwittingly) to emphasize the conservative Islamic family law paradigm in these Islamic films'.Artikel ini fokus pada paradigma hukum keluarga Islam di beberapa film islami Indonesia. Film-film yang dimaksud adalah Ketika Cinta Bertasbih 2 (2009), Surga Yang Tak Dirindukan (2015), Talak 3 (2016), dan Wedding Agreement (2018). Artikel ini menyajikan diskusi isu hukum keluarga yang direka dalam beberapa film tersebut, di mana tujuannya adalah untuk menemukan seperti apa kecenderungan hukum keluarga yang dihadirkan. Penelitian ini memanfaatkan pendekatan analisis isi (content analysis) secara kualitatif. Artinya, data-data dikumpulkan dengan menelaah adegan demi adegan yang berkaitan dengan isu hukum keluarga Islam dalam keempat film tersebut, kemudian dianalisis. Alhasil, artikel ini berargumen bahwa ragam isu hukum perkawinan, seperti nikah siri, poligami, talak tiga, hingga perjanjian perkawinan dalam film-film itu cenderung mengarah kepada fikih konservatif, bukan progresif. Hal ini menandakan adanya geliat mengutamakan paradigma hukum keluarga Islam yang bernalar konservatif dalam film-film tersebut, terlepas apakah itu disengaja atau tidak.